Multi‐modal biomarkers improve prediction of memory function in cognitively unimpaired older adults. (20th December 2022) - Trelle, Alexandra N; Tran, Tammy T; Wilson, Edward N.; Deutsch, Gayle; Sha, Sharon; Andreasson, Katrin I.; Carr, Valerie A; Kerchner, Geoffrey A.; Mormino, Elizabeth C.; Wagner, Anthony D
Abstract: Background: Identifying biomarkers that predict current and future cognition may improve estimates of Alzheimer's disease risk among cognitively unimpaired older adults (CU). In vivo measures of amyloid and tau protein burden and task‐based functional MRI measures of core memory mechanisms, such as the strength of cortical reinstatement during remembering, have each been linked to individual differences in memory in CU. This study assesses whether combining CSF biomarkers with fMRI indices of cortical reinstatement improves estimation of memory function in CU, assayed using three unique tests of hippocampal‐dependent memory. Method: Participants were 157 CU (90F, aged 60‐88 years, CDR=0) enrolled in the Stanford Aging and Memory Study (SAMS). Cortical reinstatement was quantified using multivoxel pattern analysis of fMRI data collected during completion of a paired associate cued recall task. Memory was assayed by associative cued recall, a delayed recall composite, and a mnemonic discrimination task that involved discrimination between studied 'target' objects, novel 'foil' objects, and perceptually similar 'lure' objects. CSF Aβ42, Aβ40, and p‐tau181 were measured with the automated Lumipulse G system (N=115). Regression analyses examined cross‐sectional relationships between memory performance in each task and a) the strength of cortical reinstatement in the Default Network (comprised of posterior medial, medial frontal, and lateral parietal regions) during associative cued recall and b) CSF Aβ42/Aβ40 and p‐tau181, controlling for age, sex, and education. For mnemonic discrimination, linear mixed effects models were used to examine the relationship between discrimination ( d') and each predictor as a function of target‐lure similarity. Result: Stronger cortical reinstatement was associated with better performance across all three memory assays. Age and higher CSF p‐tau181 were each associated with poorer associative memory and a diminished improvement in mnemonic discrimination as target‐lure similarity decreased. When combined in a single model, CSF p‐tau181 and Default Network reinstatement strength, but not age, explained unique variance in associative memory and mnemonic discrimination performance, outperforming the single‐modality models. Conclusion: Combining fMRI measures of core memory functions with protein biomarkers of Alzheimer's disease significantly improved prediction of individual differences in memory performance in CU. Leveraging multimodal biomarkers may enhance future prediction of risk for cognitive decline.